PENINGKATAN PEMAHAMAN MASYARAKAT TERKAIT DENGAN PERAN KAPASITAS HUKUM DALAM MELAKUKAN PERJANJIAN DAN KONTRAK UNTUK MEWUJUDKAN KEPASTIAN HUKUM DAN KEADILAN BAGI PARA PIHAK - Hartana (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2023)
This community service article aims to provide knowledge and increase understanding to the public regarding the role of legal capacity in entering into agreements and contracts to create legal certainty and justice for the parties. An agreement is an agreement by which one or more parties bind themselves to one or more people. The rise in cases of disputes that occur as a result of unclear or invalid agreements has resulted in many ordinary people and those who are not competent in the law suffering losses because of this. Several other factors also underlie the occurrence of these disputes and problems, one of which is the lack of legal capacity to enter into an agreement or contract. The method used in this community service process is by conducting outreach and outreach with the community through focus group discussions. To increase public understanding regarding the role of legal capacity in entering into agreements and contracts, several steps can be taken, such as legal education, public information, advocacy and collaboration. So, in order to realize legal certainty and justice for the parties to agreements and contracts, increasing public understanding regarding the role of legal capacity is very important. With a better understanding of legal capacity, people can make legal and binding agreements and contracts, as well as understand the legal consequences that may arise from these agreements or contracts. A better understanding of legal capacity can also help people protect their interests in agreements and contracts